Fertility Preservation and Restoration Options for Pre-Pubertal Male Cancer Patients: Current Approaches - Eugeni, Elena; Arato, Iva; Del Sordo, Rachele; Sidoni, Angelo; Garolla, Andrea; Ferlin, Alberto; Calafiore, Riccardo; Brancorsini, Stefano; Mancuso, Francesca; Luca, Giovanni (Frontiers in Endocrinology, 2022)
Fertility preservation for prepubertal male patients undergoing gonadotoxic therapies, potentially depleting spermatogonial cells, is an expanding necessity, yet most of the feasible options are still in the experimental phase. We present our experience and a summary of current and novel possibilities regarding the different strategies to protect or restore fertility in young male patients, before proceeding with chemotherapy or radiotherapy for malignances or other diseases. Adult oncological patients should always be counselled to cryopreserve the semen before starting treatment, however this approach is not suitable for prepubertal boys, who aren’t capable to produce sperm yet. Fortunately, since the survival rate of pediatric cancer patients has skyrocketed in the last decade and it’s over 84%, safeguarding their future fertility is becoming a major concern for reproductive medicine. Surgical and medical approaches to personalize treatment or protect the gonads could be a valid first step to take. Testicular tissue autologous grafting or xenografting, and spermatogonial stem cells (SSCs) transplantation, are the main experimental options available, but spermatogenesis in vitro is becoming an intriguing alternative. All of these methods feature both strong and weak prospects. There is also relevant controversy regarding the type of testicular material to preserve and the cryopreservation methods. Since transplanted cells are bound to survive based on SSCs number, many ways to enrich their population in cultures have been proposed, as well as different sites of injection inside the testis. Testicular tissue graft has been experimented on mice, rabbits, rhesus macaques and porcine, allowing the birth of live offspring after performing intracytoplasmic sperm injection (ICSI), however it has never been performed on human males yet. In vitro spermatogenesis remains a mirage, although many steps in the right direction have been performed. The manufacturing of 3D scaffolds and artificial spermatogenetic niche, providing support to stem cells in cultures, seems like the best way to further advance in this field